The Middle Paraná River Limnology of a Subtropical Wetland - Iriondo, Martin H.; Paggi, Juan César; Parma, María Julieta (Springer Berlin Heidelberg : Imprint: Springer, 2007)
1 2 2,3 MARTÍN H. IRIONDO , JUAN CÉSAR PAGGI , AND MARÍA JULIETA PARMA 2 The great Paraná basin (2,600,000 km) covers a large portion of the Neotropical Realm, extending from the Andes to the Atlantic coast and c- necting the central regions of South America along 2,200 km in a north-south direction. Most of the basin is under subtropical climates, which range from desertic in the west to humid in the east. The Middle Paraná is a broad, complex floodplain extending 600 km in the heart of the interior lowlands of the continent. This system of river channels, shallow lakes, islands, and wetlands remains unoccupied by man and basically unaltered. From a systemic point of view, this area can be considered to be the most important link and collector of the fluvial chain that conveys huge volumes of nutrients, sediments, and salts from the continent to the South Atlantic Ocean. The influence of the Paraná upon the Atlantic is very important. It has been 2 calculated that a sediment deposit 400 m thick and 1 million km in area ac- mulated in the platform and nearby oceanic bottom over the last 2 million years, with a similar amount of dissolved salts contributed by the river to the ocean. This book details the recent advances in the knowledge of the most important segment of the Parana River, organized according to the scientific structure of the National Institute of Limnology of Argentina (INALI-CONICET-UNL).